Evaluating the Psychometric Properties of the Exercise Dependence Scale-Revised (EDS-R) in a Spanish Sample - Pujals, Constanza; Baile, José Ignacio; González Calderón, María José (Pensando Psicología, 2018)
Introduction: There are several instruments to evaluate behavioural addictions. Furthermore, several specific scales have been developed to assess various aspects of exercise dependence. Nevertheless, in Spain there is a lack of specific instruments designed to assess exercise dependence. Objective: This study aims to examine the psychometric properties of a Spanish version of the Exercise Dependence Scale-Revised. Method: 175 university students who were regular exercisers (M=59.11, SD=15.89) took part in the study. They were requested to complete the EDS-R, as well as the General Addiction Scale. The requirement to take part in the study was to exercise a minimum of four times per week. Results: Findings provide initial support for the psychometric properties of the scale as its internal consistency (Cronbach’s alpha: 0.907), and construct and convergent validity with the EAG-RC (r=.559; p<.001) are adequate. In addition, its structure did not need to be modified, as it kept the 21 original items from the American version. Factor analysis yielded a five-factor structure (tolerance, loss of control, continuity, intensity, and withdrawal symptoms) which differ from the ones obtained in the original (American) and French versions where seven factors were obtained. This correlated five-factor model explains 50% of the variance. Conclusion: This Spanish EDS-R, which presents adequate psychometric properties, will provide researchers and clinicians with specific data on this screening tool for assessing exercise dependence. Further research is needed to confirm the current results and check its validity both in research and clinical practice.